Strategies for teaching oral communication to intermediate level adults, learning english as a foreign language in a language center - Serrano Martínez, Kenia Nayósqui (UDELAS, 2009)
Of all the four skills (listening, speaking, reading and writing), speaking seems intuitively the most importan: people who know a language are referred to as "speakers" of that language, in this way we have seem manu foreign language learners who are interested in learningnto speak, mainly adults who are looking for a variety of opportunities, abilities and quality that a new language can offer to them.